Influence of vacuum annealing on the composition of electrochemically deposited zinc selenide layers - Klochko, N.P.; Volkova, N.D.; Dobrotvorskaya, M.V.; Mateychenko, P.V.; Kopach, V.R.; Shkaleto, V.I.; Karasyov, S.N. (Functional Materials, 2005)
The paper is devoted to the analysis of electrodeposited zinc selenide films compositions and to the research of their homogenization and purification probabilities by vacuum annealing. In order to investigate the surface morphology and the composition of electrodeposited films electron-probe microanalysis and X-ray photoelectron spectroscopy (XPS) methods were used. It was revealed that as-electrodeposited films were enriched with selenium and consisted of ZnSe and Zn(OH)₂, covered with Se, SeO₂ and OSe(OH)₂ layers. The film compositions before annealing were not homogenous. There were friable conglomerates, consisting mostly of Zn(OH)₂, on their surfaces. Vacuum annealing at 100-350°C provided for Zn(OH)₂ transformation into ZnO, for water removing from the films and partially for the desorption of oxygen and selenium. The second part of surplus selenium in the chemical state of Se, SeO₂ and OSe(OH)₂ during the vacuum annealing at 350°C interacted with Zn(OH)₂ or ZnO and hydrogen occluded in the films due to supplementary cathode process of water reduction. As a result of such interaction, ZnSe was obtained. The friable conglomerates after the annealing were enriched by selenium that also led to the generation of ZnSe.